Effect of enzyme and inoculant additives on preservation and feeding value of wheat and forage sorghum silages - Laytimi, A.; Bolsen, K.; Schurhammer, J.; Kirch, B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Enzyme and inoculant additives produced more efficiently preserved wheat and forage sorghum silages and improved their feeding value. In general, treated silages had lower pH, acetic acid, and ammonia-nitrogen values and higher lactic acid and lactic to acetic acid ratios than untreated silages. In two of the three trials, cell wall and acid detergent fiber fractions were lower in treated than untreated silages. In Trial 2, the treated sorghum silages were extremely unstable in air and cattle performance was similar for control and treated silages. In Trial 3, gains and feed conversions in steers were improved for those fed treated forage sorghum silages.
Keywords: Beef; Wheat; Forage sorghum silages; Feed value; Enzyme; Inoculant additives